Mosque Financial Accountability and the Implementation of Sharia Accounting: A Qualitative Study in South Kalimantan, Indonesia - Abd. Adim; A. Hafiz Anshary; Zaki Mubarak (At-Taradhi Jurnal Studi Ekonomi, 2026)
Mosque financial governance in South Kalimantan, Indonesia, remains constrained by limited administrator understanding of Sharia accounting, concentrated organisational authority, and uneven regulatory implementation, despite the province recording 2,900 mosques and clear normative expectations under Kepdirjen DJ.II/802/2014. This study examines how the implementation of Sharia accounting affects mosque financial accountability and identifies the institutional and human-resource conditions that enable or constrain it. A qualitative case study design was used, drawing on semi-structured interviews, non-participant observation, and document analysis across six mosques of differing typology in Banjarmasin and Banjar Regency, analysed through Miles and Huberman's (1994) interactive model with source and method triangulation. The findings show that limited implementation support for ISAK 35 (rather than lack of awareness), overlapping chairperson–treasurer roles, and weak congregant engagement — more than resource scarcity alone — account for the persistent gap between regulation and practice; where Sharia accounting is more fully applied, informants associate it with stronger transparency and congregational trust. The study recommends tiered, typology-specific reporting templates, mandatory separation of administrative roles, and routine congregant-facing reporting as practical steps toward more accountable mosque governance.